Os desafios para elaboração do plano de logística sustentável: um estudo de caso em uma universidade pública - Fagundes, Aline Daiane Gonçales (2022)
One of the topics discussed for decades is the issue of sustainability and environmental issues. For Sachs (2009) concerns about changing thinking and raising awareness about the limitation of “nature” capital and the dangers arising from aggressions to the environment are recent. However, despite these discussions being lengthy and controversial, as they interfere with the economy, mainly in industrialized countries, they had some evolution in the 60's and 70's. with sustainability, because the logic that still seems to prevail is the economic one (ZUCATTO, 2009). Thus, when re (thinking) sustainability, it is important to take a systemic look at the eight dimensions of sustainability (social, cultural, ecological, environmental, territorial, economic, national and international policy) proposed by Sachs (2009), as they are interdependent, any impact on one will reflect on the other dimensions and vice versa (ZUCATTO, 2009). Furthermore, understanding how the co-production of the public good permeates these dimensions makes it possible to verify social participation in topics such as sustainability. For Salm (2014) the co-production of the public good requires social participation in the sharing of responsibilities and production of public goods and services, with practices and values consistent with human multidimensionality and the sustainability of the biosphere. In this work, the public good was considered equivalent to sustainability. For Bobbio, Matteucci and Pasquino (1998) the public good is the search for the natural happiness of the collectivity, that is, a political value linked to ethics and morals. When public services have these characteristics, they can be considered part of the public good (SOUZA, 2015). Thus, the general objective of this dissertation was to identify the challenges in the process of elaborating the Sustainable Logistics Plan (PLS) at the Federal University of Pampa (UNIPAMPA). The PLS is a planning tool, which aims to establish sustainable practices and promote people's awareness. As for the methodology, the research was qualitative and in the content analysis, analysis categories were used – Sustainability and Co-production. In the results, it was found that 7 of the 8 dimensions were evidenced in the PLS. The dimension - International Policy was not identified, but it appears indirectly, since this dimension permeates the PLS, as it dialogues with the UN's sustainable development goals (SDGs) (MAPA, 2019). As for co-production, there was no social participation in the constitution of the PLS implementation commission, so it was not possible to fit into one of the typologies of co-production of the public good. Furthermore, the institution's campuses did not participate in the process, remaining only within the scope of the Rectory. This phenomenon can be identified as neo-institutionalism, which aims to meet the regulatory framework, from a Strategic Management perspective. In view of this, it should be noted that the Covid 19 pandemic greatly limited the mobilization of people in social phenomena and processes. Finally, it is suggested that social participation can receive more and more attention from the Institution in the construction and provision of public services, especially in actions aimed at encouraging and disseminating sustainable practices such as the PLS.